Morbidity and mortality of infant of diabetic mothers - Aziz, Abdul; Annamalai, Thumjaa; Ahmed M., Shafath (International Journal of Contemporary Pediatrics, 2018)
Background: Diabetes mellitus is a chronic metabolic disorder due to either insulin deficiency (relative or absolute) or due to peripheral tissue resistance to the action of insulin. Women are classified into those who were known to have diabetes before pregnancy as Pregestational or overt, and those diagnosed during pregnancy as Gestational. The study was conducted in infants born to diabetic mothers focusing on the morbidity and mortality of the neonates. Methods: This is a cross-sectional study which was carried out in the Neonatal Unit, Department of Pediatrics, Sree Balaji Medical College and Hospital from July 2014 to July 2015. The study population comprises of 65 Neonates of mothers diagnosed to have gestational diabetes mellitus or overt diabetes mellitus. Screening and appropriate investigations was done for the neonates. Results: 65 neonates of Infants of Diabetic Mother were studied, 48(73.85%) were born to mothers with Gestational Diabetes Mellitus and 17 (26.15%) were born to mothers with Overt Diabetes Mellitus. The most common morbidity in neonate born to GDM mothers compared to overt DM mothers was hyperbilirubinemia (52.08%), hypoglycaemia (50%), polycythemia (43.75%). Ventricular septal defect (17.65%) was the most common cardiac finding in overt DM mothers. P values (0.05%) were significant for hyperbilirubinemia, hypoglycaemia and polycythemia when compared with infants of GDM mothers and overt DM mothers. There was no mortality in present study. Conclusions: The occurrence of morbidities and mortality were more significant in the infants of GDM mothers when compared to overt DM mothers who had good glycemic control before and during the pregnancy.